Kemandirian Ekonomi Warga Binaan Balai Rehabilitasi Sosial Eks Gelandangan dan Pengemis (BRSEGP) Pangudi Luhur di Kota Bekasi, Jawa Barat - Anggarini, Putri; Solihin, Muhtar Mochamad (Islamic Extension Guidance Study Program (BPI) of the Faculty of Da'wah and Communication, 2022)
Abstract: Poverty is one of the factors of urbanization. Unfortunately, there are so many people who urbanize to big cities without adequate education, experience and skills so that many of them fail to make a career and make a living in the city and end up being homeless and beggars. The government through the government regulation of the Republic of Indonesia Number 31 of 1980 seeks to overcome the phenomenon of homeless people and beggars by establishing rehabilitation centers and holding mental and spiritual training in them. Therefore, the purpose of this study is to 1) explain the process of spiritual mental development carried out by religious mentors to foster sprawl independence at BRSEGP Pangudi Luhur Bekasi 2) analyze the supporting and inhibiting factors faced in the process of mental spiritual development at BRSEGP Pangudi Luhur Bekasi. This research uses a qualitative approach with a case study method. The research informants were taken by purposive sampling technique as many as 8 informants; 1 (one) religious advisor, 3 (three) social workers, 4 (four) homeless people and beggars. The results showed that 1) the process of implementing mental spiritual development at BRSEGP Pangudi Luhur Bekasi was carried out for two hours every Monday, Wednesday and Friday night and the methods used were lectures, question and answer methods, and demonstration methods, 2) supporting factors in the process. spiritual guidance is a mentor and coach who is experienced and understands the material, the material is easy to understand, the friendliness of the coach and mentor and the willingness to change in the homeless and beggars. The inhibiting factors include the indiscipline of homeless people and beggars, activities can only be followed by homeless people and beggars who don't work, lack of facilities and differences in education levels of homeless people and beggars.Abstrak: Kemiskinan merupakan salah satu faktor terjadinya urbanisasi. Sayangnya banyak sekali penduduk yang melakukan urbanisasi ke kota besar tanpa persiapan pendidikan, pengalaman dan keterampilan yang memadai sehingga banyak dari mereka yang gagal untuk berkarir dan mencari penghidupan di kota dan berakhir menjadi gelandangan dan pengemis (gepeng). Pemerintah melalui peraturan pemerintah Republik Indonesia Nomor 31 Tahun 1980 berupaya menanggulangi fenomena gepeng dengan mendirikan panti-panti rehabilitasi dan mengadakan peminaan mental spiritual di dalamnya. Maka dari itu tujuan penelitian ini untuk 1) menjelaskan proses pembinaan mental spiritual yang dilakukan pembimbing agama untuk menumbuhkan kemandirian gepeng di BRSEGP Pangudi Luhur Bekasi 2) menganalisis faktor pendukung dan penghambat yang dihadapi pada proses pembinaan mental spiritual di BRSEGP Pangudi Luhur Bekasi. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Adapun informan penelitian diambil dengan teknik purposive sampling sebanyak 8 orang informan; 1 (satu) orang pembimbing agama, 3 (tiga) orang pekerja sosial, 4 (empat) orang gepeng. Hasil penelitian menunjukkan bahwa 1) proses pelaksanaan pembinaan mental spiritual di BRSEGP Pangudi Luhur Bekasi di laksanakan selama dua jam setiap hari Senin, Rabu dan malam Jumat dan metode yang digunakan adalah ceramah, metode Tanya jawab, dan metode demonstrasi, 2) faktor pendukung dalam proses pembinaan spiritual adalah pembimbing dan pembina yang berpengalaman dan memahami materi, materi mudah dipahami, keramahan pembina dan pembimbing dan adanya kemauan untuk berubah pada diri gepeng. Adapun faktor penghambat meliputi ketidak disiplinan gepeng, kegiatan hanya bisa diikuti gepeng yang tidak bekerja, kurangnya fasilitas dan perbedaan tingakat pendidikan gepeng.